The Concept and Content of Teacher’s Reflective Practice: From Impulsiveness of Professional Activity towards Personal and Professional Development - Bubnys, Remigijus; Kairienė, Aida (Pedagogika, 2016)
Reflective practice as one of the key factors determining changes in the teacher’s performance in a learning organization requires a careful study, focusing on aspects of creation of favourable learning environment at school. In order to analyse the concept of the teacher’s reflective practice, it is relevant to answer this problem question: How is the teacher’s reflective practice characterized and what is its content? The research aim is to analyse the concept of reflective practice in the pedagogical context, distinguishing essential characteristics of the concept: attributes, antecedents, consequences. The research method is a systematic analysis of literature, using Rodgers’ (1989) method of evolutionary concept analysis. The theoretical analysis of the teacher’s reflective practice enabled to distinguish features that are directly associated with experiential learning, deep critical thinking, investigation of personal actions, professional and personal development. The disclosed antecedents of the concept are: reflection on experience, endeavour of reflection and the need to evaluate thinking and investigate one’s professional actions, endeavour of self-efficacy, knowledge and awareness, and the needs of improvement of teaching and learning, professional growth and renewal, personal integrity. Outcomes of the teacher’s professional and personal development were formulated. Research results enable to generalise that the teacher’s reflective practice is a complex concept, encompassing dimensions of experiential learning, critical thinking, reflective teaching / learning and investigation, related to the teacher’s professional and personal development.